Enhanced Interfacial Bonding and Mechanical Properties of Short Fiber‐Reinforced CF – PLA via Multidirectional Ultrasonic Vibration‐Assisted FDM - Zhao, Yanbo; Xu, Zhicheng; Ding, Qingjun; Zhao, Gai; Li, Huafeng; Yang, Ling; Wang, Guoqing (Polymer composites, 2025)
To enhance the interfacial bonding quality and mechanical performance of fused deposition modeling (FDM) short carbon fiber‐reinforced polylactic acid (CF–PLA) composites, this study proposes a multidimensional ultrasonic vibration‐assisted printing strategy. A self‐developed vibration‐assisted 3D printing platform was employed to investigate the effects of Z ‐direction, Y ‐direction, and Z + Y bidirectional coupled vibrations on print quality, porosity, surface roughness, fiber orientation, and mechanical properties. Results revealed that moderate unidirectional vibrations improved interlayer ( Z ‐direction) and inter‐filament ( Y ‐direction) fusion, while bidirectional coupled vibration showed a synergistic enhancement in melt disturbance, fiber realignment, and microstructural densification. Compared to non‐vibrated samples, bidirectionally vibrated specimens exhibited 42.7%, 46.2%, and 65.2% improvements in tensile, flexural, and impact strengths, respectively. Additionally, porosity decreased from 17.87% to 7.09%, median pore size reduced from 126.85 to 22.95 μm, and surface roughness dropped to 12.30 μm. Fracture surface scanning electron microscopy (SEM) analysis further confirmed that multidimensional vibration facilitated directional fiber orientation and improved interfacial continuity. This work integrates multi‐axis ultrasonic excitation into the FDM process, revealing direction‐dependent fusion behavior and significant synergy under bidirectional conditions. These findings provide theoretical support and practical guidance for enhancing interface quality and mechanical reliability in short fiber‐reinforced 3D printed composites.